2018
DOI: 10.1002/msc.1230
|View full text |Cite
|
Sign up to set email alerts
|

From “Non‐encounters” to autonomic agency. Conceptions of patients with low back pain about their encounters in the health care system

Abstract: Low back pain is a considerable health problem which affects people around the world, causing major healthcare costs. The use of qualitative research methods enables us to describe and understand patients' experience of, and attitudes to, healthcare. The aim of the present phenomenographic study was to identify and describe the contextual nature of the conceptions of patients with low back pain of their encounters in the HCS. Seventeen patients with chronic or episodic low back pain classified as "high risk" w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 25 publications
1
28
0
2
Order By: Relevance
“…Our participants widely described the trust that they felt in both the therapists and the program. Other studies have also shown that trust is important in the working alliance from the perspectives of the therapists as well the patients [20,54,55]. Furthermore, Røkenes and Hansen [53] underlined the importance of their therapists' ability to act as a container for the patients' feelings, which is important in the development of a strong and trusting bond in the alliance; this concept was also pointed out in Bordin's [26] conceptual framework.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Our participants widely described the trust that they felt in both the therapists and the program. Other studies have also shown that trust is important in the working alliance from the perspectives of the therapists as well the patients [20,54,55]. Furthermore, Røkenes and Hansen [53] underlined the importance of their therapists' ability to act as a container for the patients' feelings, which is important in the development of a strong and trusting bond in the alliance; this concept was also pointed out in Bordin's [26] conceptual framework.…”
Section: Discussionmentioning
confidence: 98%
“…Interestingly, the participants felt that they were "in charge", despite their vulnerability and the imbalance of power in the relationship. Holopainen [55], who investigated the encounters of patients with low back pain in the health care system, had a patient state the following to healthcare professionals: "Put us in charge, with you working as a coach" (page 275). Nevertheless, our participants were in fact vulnerable, and our findings suggest that their vulnerability made trust essential.…”
Section: Discussionmentioning
confidence: 99%
“…Wijma, Van Wilgen, Meeus, and Nijs (), for example, describes the importance of the assessment process to explore biopsychosocial pain contributing factors to subsequently ‘tailor education’ to individualise the management approach for people with chronic pain. Holopainen, Piirainen, Heinonen, Karppinen, and O'Sullivan (), in their phenomenographic paper, discussed the conceptions of ‘patients’ with NSLBP about their encounters in the health care system. Participants valued a shared understanding of their pain and a strong therapeutic relationship to facilitate an active role in their own rehabilitation.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Jessica particularly addressed ‘patient’ reassurance as a key element of PE, ultimately linked to encouragement for physical activity. The importance of reassurance has been noted in recent literature which established that reassuring people with NSLBP to engage in exercise, as part of PE, encourages autonomic agency and pro‐active recovery (Holopainen et al, ). As highlighted in another study, a focus on reassurance as part of PE may also have further implication for healthcare costs (Traeger et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The WHO Global Competency Model (2012) states core qualities that are related to ethical competence: active listening, responsibility for one's own work, ability to identify conflicts, respecting others' individuality, acting confidentially and according to the ethical and legal framework and personal values [17]. Important is being present, empathetic and supportive and having a reciprocal relationship with patients [18]. Among the core competences in physiotherapy defined in a Finnish survey/Delphi study [19] the ethical aspects were addressed as important and especially ethical sensitivity will be emphasized in the future.…”
Section: Introductionmentioning
confidence: 99%